INFORMASI ASIMETRI DALAM PRODUK MUDHARABAH - Satiri (Pasca Sarjana Universitas Satya Negara Indonesia, 2018)
At the beginning of the development of Islamic economics, Islamic scholars hold the principle of Islamic law in economy that is the profit and loss sharing, because interest is forbidden in Islam. The first product called mudharabah, is purely the profit and loss sharing product. The product growth is not really good, even the proportion of the product decreasing compare to other product like murabahah (the cost plus trading). The stagnancy of mudharabah mostly because there is asymetric information on the contract between the capital owner (shohibul mal) and the executive (mudharib). The owner does not know full information about the project that is done by the executive. Therefore many mudharabah contact fail in the middle causing the stagnancy of the development of the product.